Mortality after a cholecystectomy: a population‐based study. Issue 3 (March 2015) - Sandblom, Gabriel; Videhult, Per; Crona Guterstam, Ylva; Svenner, Annika; Sadr‐Azodi, Omid
Abstract: Background: The trade‐off between the benefits of surgery for gallstone disease for a large population and the risk of lethal outcome in a small minority requires knowledge of the overall mortality. Methods: Between 2007 and 2010, 47 912 cholecystectomies for gallstone disease were registered in the Swedish Register for Cholecystectomy and endoscopic retrograde cholangiopancreatography (ERCP) (GallRiks). By linkage to the Swedish Death Register, the 30‐day mortality after surgery was determined. The age‐ and sex‐standardized mortality ratio (SMR) was estimated by dividing the observed mortality with the expected mortality rate in the Swedish general population 2007. The Charlson Comorbidity Index (CCI) was estimated by International Classification of Diseases (ICD) codes retrieved from the National Patient Register. Results: Within 30 days after surgery, 72 (0.15%) patients died. The 30‐day mortality was close [SMR = 2.58; 95% confidence interval (CI): 2.02–3.25] to that of the Swedish general population. In multivariable logistic regression analysis, predictors of 30‐day mortality were age >70 years [odds ratio (OR) 7.04, CI: 2.23–22.26], CCI > 2 (OR 1.93, CI: 1.06–3.51), American Society of Anesthesiologists (ASA) > 2 (OR 13.28, CI: 4.64–38.02), acute surgery (OR 10.05, CI:2.41–41.95), open surgical approach (OR 2.20, CI: 1.55–4.69) and peri‐operative complications (OR 3.27, CI: 1.74–6.15). Discussion: Mortality after cholecystectomy is low. Co‐morbidity and peri‐operative complications may, however, increase mortality substantially. The increased mortality risk associated with open cholecystectomy could be explained by confounding factors influencing the decision to perform open surgery.